A phase 3 randomized placebo-controlled trial of tadalafil for Duchenne muscular dystrophy - Victor, RG; Sweeney, HL; Finkel, R; McDonald, CM; Byrne, B; Eagle, M; Goemans, N; Vandenborne, K; Dubrovsky, AL; Topaloglu, H; Miceli, MC; Furlong, P; et al. (Wolters Kluwer Health, Inc., 2017)
Objective: To conduct a randomized trial to test the primary hypothesis that once-daily tadalafil, administered orally for 48 weeks, lessens the decline in ambulatory ability in boys with Duchenne muscular dystrophy (DMD).